Distributed reputation management for service-oriented peer-to-peer enterprise communities. (2016) - Amoretti, Michele; Zanichelli, Francesco
Peer-to-peer service sharing might allow for unmediated, almost instantaneous inter-firm collaboration, yet robust reputation management techniques are strongly required to withstand fraudulent actions of malicious peers. In this paper we illustrate a distributed reputation management system for service-oriented peer-to-peer networks, called SAFE, which exploits voting and effectively copes with trust misrepresentation attempts. Simulation results show that SAFE allows peers to select high-quality services, even when a large number of malicious providers and advisors are active in the community.